Une possible ouverture patrimoniale de futurs inédits au-delà du présentisme - Géraldine Djament (Temporalités)
This article proposes to re-examine relationships between “presentist” historicity regime and contemporary patrimoniality regime based on a study of the ongoing conflict over the heritage of the former Reille convent, in the 14th arrondissement of Paris, which is awaiting reuse and/or a property development project. This wasteland is studied as revealing the fragility and temporal apories of the “all-heritagization”, which is characterized by an unprecedented disassociation of heritage recognition and protection, by a diversification of heritage processes and even by a paradox but necessary heritage by reuse. The breach of time opened by the defunctionalization of the convent is extended by a process of multiform heritagization, led in particular by the local residents mobilized, and establishes, on the occasion of the revision of the local urban plan of the city of Paris, a fruitful waiting time, conducive to the development of a heritage, social and environmental reuse project alternative to the real estate development project. Finally, the rise in generality of heritage mobilization networked at the metropolitan scale shows that different trends coexisting within the contemporary heritage regime can arise “new futures”, an alternative horizon of expectation for the metropolis.